Crystalline structure and thermal property characterization of chitin from Antarctic krill (Euphausia superba) - Wang, Yanchao; Chang, Yaoguang; Yu, Long; Zhang, Cuiyu; Xu, Xiaoqi; Xue, Yong; Li, Zhaojie; Xue, Changhu (Carbohydrate Polymers, 2013)
Antarctic krill (Euphausia superba) has been widely studied and extensively recognized as a target for commercial fishing. In this study, Antarctic krill chitin was extracted from defatted Antarctic krill shell, and its crystalline structure and thermal properties were characterized by employing Fourier transform infrared spectroscopy, X-ray diffractometry, scanning electron microscopy, thermogravimetry, and differential scanning calorimetry. Results showed that Antarctic krill chitin corresponded to the α-polymorph, and was composed of small, stable, and uniform microcrystals. The degree of N-deacetylation was 11.28 ± 0.86%. The d-spacings of Antarctic krill chitin were 9.78 Å and 4.63 Å at (0 2 0) and (1 1 0) planes. The crystalline sizes were 6.07 nm and 5.16 nm at (0 2 0) and (1 1 0) planes, respectively. The activation energy of the polysaccharide chain decomposition was 123.35 kJ/mol and the glass transition (T) of Antarctic krill chitin was 164.96 °C.